Personality impairment in the DSM-5 and ICD-11: Current standing and limitations. Issue 1 (January 2021) - Sleep, Chelsea; Lynam, Donald R.; Miller, Joshua D.
Abstract : Purpose of review: The current review provides an examination of the levels of personality functioning outlined by the International Classification of Diseases-11 and the 5th edition of the Diagnostic and Statistical Manual of Mental Disorders . Recent findings: Across self-report measures, high convergence is observed, and they evince relatively robust relations with general and pathological traits as well as other clinical symptoms. At the same time, current measures of impairment also demonstrate unstable factor structures, poor discriminant validity (when measures offer subscales aligned with different forms of personality impairment), and tend to account for relatively little unique variance beyond traits. As a result, some have questioned the utility of personality impairment, as currently measured. Summary: The dimensional models of personality psychopathology included in the International Classification of Diseases-11 and 5th edition of the Diagnostic and Statistical Manual of Mental Disorders signify important steps toward an empirically supported and clinically useful diagnostic model; however, self-report measures of impairment are problematic. The authors conclude by calling for the refinement of these measures to more directly assess deficits in various domains of functioning as well as the dimensional models, by assessing traits first, and then examining the nature of the associated personality impairment.